Prevalence and Diversity of Ectoparasites in African Catfish (Clarias gariepinus) Cultured in Freshwater Ponds of Lampung, Indonesia - Alkausar, Triawan; Aini, Azizah Nurul; Ulmillah, Aulia; Putra, Rizki Pratama; Waddell, Nawaporn (WISE Pendidikan Indonesia, 2025)
Ectoparasitic infestations pose a significant threat to the sustainability of aquaculture systems, particularly affecting African catfish (Clarias gariepinus), a species intensively cultured in tropical regions, including Indonesia. This study aimed to analyze the community structure, prevalence rate, and infection intensity of ectoparasites in C. gariepinus cultured in three freshwater pond units located in Way Kandis, Lampung. Fieldwork was conducted between March and April 2023, involving 50 individuals measuring 25–30 cm in length. Fish mucus was collected from the skin, fins, and gill lamellae, followed by microscopic examination to identify ectoparasite genera and quantify infestation levels. A total of five ectoparasitic genera were identified: Oodinium, Gyrodactylus, Dactylogyrus, Chilodonella, and Trichodina. Among them, Dactylogyrus spp. showed the widest distribution across all sampling sites. The highest prevalence occurred in Pond I (46%), followed by Pond II (26%) and Pond III (10%), resulting in an overall prevalence of 86%. Mean infection intensities ranged from 1.25 to 2.00 parasites per host, with higher intensities observed in ponds exhibiting poor water quality and limited maintenance. These findings demonstrate that ectoparasitic infections remain a critical issue in small-scale aquaculture systems. The study provides important baseline data for developing targeted parasitological surveillance and management strategies. It underscores the necessity of proactive health management practices to enhance fish welfare, reduce production losses, and support sustainable aquaculture development in tropical pond-based systems.